Philosophy of Law and Legal Theory Historical and Contemporary Perspectives - Theme "Justice Based on Truth" - Senn, Marcel (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint deals with the central theme of philosophy of law and legal theory, namely the relationship between truth and justice. This presupposes that we always have true knowledge-that is, verifiable facts-and the intellectual ability to theoretically and historically correctly ascertain and analyse the question of justice. A modern philosopher of law who has formulated this issue excellently in his work is Ronald Dworkin (1931-2013). Therefore, he is the common point of reference for all our contributions to "Justice based on Truth". In addition, great philosophers of the past such as Thomas Aquinas, Baruch de Spinoza, Gottfried Wilhelm Leibniz or Lon Fuller, to whom our authors devote themselves, have commented on these questions. Finally, time-tested folk wisdom such as the traditional Chinese doctrine of the use of stratagems in life or the modern theory of transitional justice in civil war-like conflicts can also perform these functions.